Peluang Usaha "Pembuatan Sabun Cuci Piring" Untuk Meningkatkan Pendapatan Keluarga Di Kelurahan Paropo Kec. Panakukang Kota Makassar - Wa Ode Rustiah; St. Chadijah; Maswati Baharuddin; Sjamsiah Sjamsiah (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2020)
Abstract The problem that occurs in the Paropo sub-district, Panakkukang district, Makassar, is the large number of family heads with high dependence on the using of cleaning soap from dirt on an object. The results of a conducted survey, people generally switch to using liquid dishwashing soap, due to the many advantages of liquid soap, also practical because it is available in bottle form. However, limited funds, lack of knowledge about chemicals how to make liquid soap, and how to make it, until finally becoming an obstacle in opening up business opportunities going forward. The material was delivered through counseling using a combination of lecture, discussion and evaluation methods, and also continued to provide training with demonstrations on how to make liquid soap. From the community service activities, it provides enormous benefits to the community. It can be seen from the community's desire to make liquid soap independently for use among their families. Then start ordering raw materials to provide guidance in terms of good and durable packaging, so that this activity becomes a mover in marketing the results of the home industry.